2019
DOI: 10.1038/s41420-019-0195-1
|View full text |Cite
|
Sign up to set email alerts
|

Avenanthramide-C prevents noise- and drug-induced hearing loss while protecting auditory hair cells from oxidative stress

Abstract: Noise exposure or ototoxic drugs instigate various types of damage to the cochlea, resulting in hearing loss (HL). While the incidence of HL is growing continuously, there are, so far, no adequate drugs to prevent or treat HL. Avenanthramide (AVN), a natural product extracted from oats, has been reported to possess anti-oxidant/inflammatory properties, and protect several types of cells. In this study, we investigated whether AVN-C can protect auditory hair cells, and preserve hearing from noise trauma and oto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Taking into consideration previous studies regarding the therapeutic effects of GV1001, we hypothesized that GV1001 might also exert otoprotective effects against NIHL, because excessive ROS/RNS generation and its signaling cascades, involving inflammatory and cell stress or apoptosis pathways are thought to underlie the causative mechanisms of NIHL. In support of this hypothesis, Avenanthramide-C that possesses antioxidant and anti-inflammatory properties was shown to exhibit a similar protective effect against noise-and drug-induced ototoxicity in the mouse model [15]. To the best of our knowledge, there have been no studies regarding the therapeutic effects of peptide vaccine GV1001 on NIHL.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Taking into consideration previous studies regarding the therapeutic effects of GV1001, we hypothesized that GV1001 might also exert otoprotective effects against NIHL, because excessive ROS/RNS generation and its signaling cascades, involving inflammatory and cell stress or apoptosis pathways are thought to underlie the causative mechanisms of NIHL. In support of this hypothesis, Avenanthramide-C that possesses antioxidant and anti-inflammatory properties was shown to exhibit a similar protective effect against noise-and drug-induced ototoxicity in the mouse model [15]. To the best of our knowledge, there have been no studies regarding the therapeutic effects of peptide vaccine GV1001 on NIHL.…”
Section: Introductionmentioning
confidence: 92%
“…GV1001 is also neuroprotective against beta-amyloid oligomers in neural stem cells, attributable to induction of cellular proliferation, anti-apoptotic and antioxidant effects, and mitochondrial stabilization [23]. Hence, this novel peptide vaccine may have additional potential applications in other medical conditions such as sudden sensorineural hearing loss or Meniere disease on the basis of the multipotent actions on the reduction of ROS/RNS, pro-inflammatory mediators and blocking proapoptotic caspases Interestingly, a recent study proposed that noise might loosen the blood-labyrinth-barrier; the highest perilymph concentration of the antioxidant AVN-C was noted 1 h after noise exposure [15]. In another study utilizing a guinea pig model, noise-induced ultrastructural changes in the blood-labyrinth barrier and decreased the immunoreactivities of tight junction proteins, suggesting that noise might affect blood-labyrinth barrier permeability [24].…”
Section: Otoprotective Effect Of Gv1001 On Nihl and Its Mechanism Assmentioning
confidence: 99%
“…Several studies show that Avn C exerts greater antioxidant activity than Avn A and B [ 16 , 17 , 18 , 38 , 39 ]. Dhakal et al [ 38 ] reported that Avn C from germinated oats exhibits anti-allergic and anti-inflammatory effects in mast cells, and Umugire et al [ 39 ] showed that Avn C exerts a strong protective effect on hearing loss caused by noise trauma. These results suggest Avn C as a promising candidate as a therapeutic for treating allergic diseases and hearing damage, given that Avn C can be provided through dietary products derived from oats.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, AVN-C has great water solubility and blood-labyrinth barrier permeability, suggesting pharmaceutical potential for NIHL treatment. Researchers have found that peritoneal injection of AVN-C protects hair cells from noise trauma by increasing antioxidant defense and decreasing proinflammatory cytokines like IL-1 β and Tnf [ 200 ].…”
Section: Therapeuticsmentioning
confidence: 99%